Pretransplant Genetic Susceptibility: Clinical Relevance in Transplant-Associated Thrombotic Microangiopathy - Gavriilaki, Eleni; Touloumenidou, Tasoula; Sakellari, Ioanna; Batsis, Ioannis; Mallouri, Despina; Psomopoulos, Fotis; Tsagiopoulou, Maria; Koutra, Maria; Yannaki, Evangelia; Papalexandri, Apostolia; Taylor, Pat; Nikolousis, Emmanuel; Stamouli, Maria; Holbro, Andreas; Baltadakis, Ioannis; Liga, Maria; Spyridonidis, Alexandros; Tsirigotis, Panagiotis; Charchalakis, Nikolaos; Tsakiris, Dimitrios A.; Brodsky, Robert A.; Passweg, Jacob; Stamatopoulos, Kostas; Anagnostopoulos, Achilles (Thrombosis and Haemostasis, 2020)
Transplant-associated thrombotic microangiopathy (TA-TMA) is a life-threatening complication of allogeneic hematopoietic cell transplantation (HCT). We hypothesized that pretransplant genetic susceptibility is evident in adult TA-TMA and further investigated the association of TMA-associated variants with clinical outcomes. We studied 40 patients with TA-TMA, donors of 18 patients and 40 control non-TMA HCT recipients, without significant differences in transplant characteristics. Genomic DNA from pretransplant peripheral blood was sequenced for TMA-associated genes. Donors presented significantly lower frequency of rare variants and variants in exonic/splicing/untranslated region (UTR) regions, compared with TA-TMA patients. Controls also showed a significantly lower frequency of rare variants in ADAMTS13, CD46, CFH, and CFI. The majority of TA-TMA patients (31/40) presented with pathogenic or likely pathogenic variants. Patients refractory to conventional treatment (62%) and patients that succumbed to transplant-related mortality (65%) were significantly enriched for variants in exonic/splicing/UTR regions. In conclusion, increased incidence of pathogenic, rare and variants in exonic/splicing/UTR regions of TA-TMA patients suggests genetic susceptibility not evident in controls or donors. Notably, variants in exonic/splicing/UTR regions were associated with poor response and survival. Therefore, pretransplant genomic screening may be useful to intensify monitoring and early intervention in patients at high risk for TA-TMA.
Keywords: transplant-associated thrombotic microangiopathy; complement; genetic susceptibility; eculizumab